Patterns of rare and abundant marine microbial eukaryotes - Logares, Ramiro; Audic, Stéphane; Bass, David; Bittner, Lucie; Boutte, Christophe; Christen, Richard; Claverie, Jean-Michel; Decelle, Johan; Dolan, John R; Dunthorn, Micah; Edvardsen, Bente; Gobet, Angélique; et al. (Current biology, 2014)
Biological communities are normally composed of a few abundant and many rare species. This pattern is particularly prominent in microbial communities, in which most constituent taxa are usually extremely rare. Although abundant and rare subcommunities may present intrinsic characteristics that could be crucial for understanding community dynamics and ecosystem functioning, microbiologists normally do not differentiate between them. Here, we investigate abundant and rare subcommunities of marine microbial eukaryotes, a crucial group of organisms that remains among the least-explored biodiversity components of the biosphere. We surveyed surface waters of six separate coastal locations in Europe, independently considering the picoplankton, nanoplankton, and microplankton/mesoplankton organismal size fractions. Deep Illumina sequencing of the 18S rRNA indicated that the abundant regional community was mostly structured by organismal size fraction, whereas the rare regional community was mainly structured by geographic origin. However, some abundant and rare taxa presented similar biogeography, pointing to spatiotemporal structure in the rare microeukaryote biosphere. Abundant and rare subcommunities presented regular proportions across samples, indicating similar species-abundance distributions despite taxonomic compositional variation. Several taxa were abundant in one location and rare in other locations, suggesting large oscillations in abundance. The substantial amount of metabolically active lineages found in the rare biosphere suggests that this subcommunity constitutes a diversity reservoir that can respond rapidly to environmental change. We propose that marine planktonic microeukaryote assemblages incorporate dynamic and metabolically active abundant and rare subcommunities, with contrasting structuring patterns but fairly regular proportions, across space and time.